If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 15 + 5x Solving 7 + -3x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 7 + -3x + -5x = 15 + 5x + -5x Combine like terms: -3x + -5x = -8x 7 + -8x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 7 + -8x = 15 + 0 7 + -8x = 15 Add '-7' to each side of the equation. 7 + -7 + -8x = 15 + -7 Combine like terms: 7 + -7 = 0 0 + -8x = 15 + -7 -8x = 15 + -7 Combine like terms: 15 + -7 = 8 -8x = 8 Divide each side by '-8'. x = -1 Simplifying x = -1
| 3-6(4+8n)=21+10n | | c(c+3)=0 | | y-(2y-5)=94 | | (3s+7)(s+6)=0 | | (3)-(-4)= | | s^2+11s+24=0 | | c^2-11c+18=0 | | 4x-7=3.5 | | -4(t+2)=12 | | s^7-7s=0 | | 32-14=3(x-4) | | -29+7x=-5(1-2x) | | 12x=6x+24 | | 12x=5x+24 | | 8y+2-6y=3+t-10 | | 5(3x-1)-3=25+4x | | z+2z= | | 12+3= | | -3x-8(1+x)=-2x+37 | | -9p(-6p+2)=-2p-9 | | 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 | | 3(4y+5)=51 | | 6(2g-5)=-6 |